2022
DOI: 10.3389/fpsyg.2022.935506
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Growth Mindset and English Language Performance Among Chinese EFL University Students: The Mediating Roles of Grit and Foreign Language Enjoyment

Abstract: There is no denying that there is ample evidence of numerous factors that influence language learners' success. Recently, there is a critical call to embrace positive psychology that is more open and appreciative of the positive influences in learning English as a foreign language (EFL). Set against this burgeoning area of study in language learning, this paper puts forward the findings of a study that aimed to examine the mediating roles of grit and foreign language enjoyment in the relationship between growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 70 publications
2
18
0
1
Order By: Relevance
“…Finally, the SEM analysis also revealed that growth mindset had significant direct effects on ELP, indicating that learners with a positive attitude regarding their capacity for language acquisition were more likely to acquire greater language proficiency. This finding also confirmed the results of other studies that showed growth mindset contributed significantly to FL performance (Hu et al, 2022;Khajavy et al, 2021). Bai and Wang (2020) noted that a person who believes that his language learning ability can be developed with hard work might be more motivated to put forth the effort and sustain effort in the face of challenges, leading to greater success in language learning.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Finally, the SEM analysis also revealed that growth mindset had significant direct effects on ELP, indicating that learners with a positive attitude regarding their capacity for language acquisition were more likely to acquire greater language proficiency. This finding also confirmed the results of other studies that showed growth mindset contributed significantly to FL performance (Hu et al, 2022;Khajavy et al, 2021). Bai and Wang (2020) noted that a person who believes that his language learning ability can be developed with hard work might be more motivated to put forth the effort and sustain effort in the face of challenges, leading to greater success in language learning.…”
Section: Discussionsupporting
confidence: 86%
“…Thirdly, the results of path analysis showed that FL enjoyment had significant direct effects on ELP, indicating that a positive classroom environment can lead to language success. This finding is supported by past studies that have found a positive link between FL enjoyment and language learning achievements (Hu et al, 2022;Li & Wei, 2022). As indicated by the broad-and-build theory, learners in an enjoyable language learning environment are more motivated to seek opportunities to learn the target language.…”
Section: Discussionsupporting
confidence: 74%
“…Además, en la concepción de los estudiantes respecto de su inteligencia influyen las prácticas de retroalimentación y la mentalidad de los adultos (Dweck, 2008;Gunderson et al, 2018), destacándose las interacciones del alumno con los docentes (Canning et al, 2019;Dweck, 2008;Shoshani, 2021) y con sus compañeros (King, 2019;Zhang et al, 2020), así como la postura del contexto familiar sobre el fracaso (Haimovitz & Dweck, 2016;Stern & Hertel, 2020). Al respecto, Hu et al (2022) resaltan la importancia de que los maestros y profesores proporcionen una retroalimentación constructiva que haga hincapié en las medidas específicas que los estudiantes deben tomar para lograr el resultado deseado, destacando la función constructiva de los fracasos, en vez de rechazarlos como una indicación de incompetencia. A su vez, Gunderson et al (2018) encontraron que elogiar el esfuerzo, la perseverancia y las estrategias empleadas, por parte de los cuidadores hacia los niños durante los años preescolares, predice las creencias de estos últimos acerca de la inteligencia y su maleabilidad, lo cual, a su vez, influye posteriormente en su ren-…”
Section: Discussionunclassified
“…Regarding the teacher, we adopted a growth mindset approach to feedback. Xiaoyu et al (2022) demonstrated an association between growth mindset and English language performance in Chinese ESL students with positive emotions being a mediating factor. Growth mindset is aligned with feedforward, a form of feedback which can be acted upon by the student in future work (Careless, 2007; Orsmond et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 92%